2014
DOI: 10.1111/j.1532-950x.2014.12150.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Postoperative Pain in Cats After Ovariectomy by Laparoscopy, Median Celiotomy, or Flank Laparotomy

Abstract: Laparoscopic ovariectomy, although slower, appeared less painful compared with conventional ventral midline and flank ovariectomy. Postoperative pain did not differ significantly between midline and flank groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 28 publications
7
39
2
4
Order By: Relevance
“…(4) When the evaluator approaches -it vocalizes and/or tries to bite 2. Touching of abdomen and flank (0) Lack of abdominal tension or no alteration in relation to response from the animal to pre-procedure touching of abdomen and flank (1) Presence of abdominal tension, it may vocalizes or tries to bite when abdomen and/or flank are touched (2) when evaluator approaches -it vocalizes and or tries to bite Factor 2: (total of 6 points) measurements did not seem to be reliable discriminators for the evaluation of postoperative pain, as reported in the study by Gauthier et al (2014) who state that physiological variables are not sound indicators of pain in cats since they are strongly influenced by other factors. In the study reported in this paper, it was observed that hypoglycemia occurred in both groups (Table 1) (Faria, 2009) at almost all times.…”
Section: Resultsmentioning
confidence: 80%
“…(4) When the evaluator approaches -it vocalizes and/or tries to bite 2. Touching of abdomen and flank (0) Lack of abdominal tension or no alteration in relation to response from the animal to pre-procedure touching of abdomen and flank (1) Presence of abdominal tension, it may vocalizes or tries to bite when abdomen and/or flank are touched (2) when evaluator approaches -it vocalizes and or tries to bite Factor 2: (total of 6 points) measurements did not seem to be reliable discriminators for the evaluation of postoperative pain, as reported in the study by Gauthier et al (2014) who state that physiological variables are not sound indicators of pain in cats since they are strongly influenced by other factors. In the study reported in this paper, it was observed that hypoglycemia occurred in both groups (Table 1) (Faria, 2009) at almost all times.…”
Section: Resultsmentioning
confidence: 80%
“…We compared this technique with OO because it is a very common procedure performed in North America for sterilizing female cats . Surgical times were longer for the laparoscopically assisted technique, which has been found in previous reports for laparoscopic sterilization in cats . This technique was the first laparoscopic procedure learned by the resident surgeon, and we believe it is a technique that could be easily used in both referral and general practices.…”
Section: Discussionmentioning
confidence: 85%
“…However, we must consider the possibility that the slightly higher heart rates of the group A and group B cats were subtle indicators of greater discomfort because penetration of the body wall musculature occurred in both group A and group B cats and may have been a source of added discomfort. Published reports comparing postoperative discomfort after flank and midline incisions for performing feline gonadectomy show conflicting results …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pneumoperitoneum with carbon dioxide was established through the laparoscope portal using a modified Hasson technique (Gauthier et al 2014). A subumbilical location through a 5-6 mm midline skin incision, using a 6.5 cm long, 6 mm trocarless threaded cannula (Ternamian Endotip; Karl Storz Veterinary Endoscopy, France), was employed to establish the camera portal.…”
Section: Laparoscopic Biopsiesmentioning
confidence: 99%